The effect of family-supportive therapy on the burden of caregivers and Activities of Daily Living among stroke patients - Nikmatul Fadilah; Loetfia Dwi Rahariyani; Hilmi Yumni; Dinarwiyata Dinarwiyata (PAGEPress Publications, 2024)
The role of family members in providing care for stroke patients at home is associated with heightened stress and burden on caregivers. Therefore, this study aimed to analyze the effect of family-supportive therapy on the burden of caregivers and Activities of Daily Living (ADL) among stroke patients. A quasi-experimental method was used with a pre-test and post-test control group. The intervention of family-supportive therapy was given to the treatment group, while the control group received home visits. Samples of 40 caregivers in two primary health care centers in Surabaya were recruited using a multi-stage sampling method. The variables were the burden of caregivers and ADL of stroke patients, while Zarit Burden's Interview Schedule and Katz Index of Independence in ADL were used as instruments. Data analysis was carried out using a Paired t-test and a Manova test. The results showed that the burden of caregivers in the treatment group decreased, but there was a re-increase after 2 weeks of therapy, and the burden in the control group also decreased. ADL of stroke patients in the treatment group increased and tended to persist up to 2 weeks after therapy, while the value in the control group decreased. Furthermore, family-supportive therapy did not have a significant effect on the burden of caregivers (p-value 0.12) and ADL (p-value 0.21). To address this challenge, modifying services through the implementation of community health programs, individual health efforts for stroke patients in the hospital and at home, group services for families providing primary health care, and home visits could be a comprehensive effort. The study found that family-supportive therapy and health education through home visits reduced caregiver burden.